The Effect of Time Pressure on Criminal Decision-Making - Cimalanskaitė-Kazlauskienė, Violeta; Valickas, Gintautas (Teisė, 2023)
The article analyzes the effect of time pressure on the decision to commit a crime based on a dual-process approach. An experiment was conducted with the participation of 67 at least once convicted adult men. All participants examined fraud scenarios with limited and unlimited time conditions for their evaluation and decided on the consent or refusal of the actor in the vignette to commit the crime. Although the decision that the actor in the situation will commit a crime prevailed regardless of the experimental conditions, the results of this study confirm that time pressure has a significant effect on information processing. Time pressure is associated with the predominance of Type 1 (automatic, intuitive) processes and suppression of Type 2 (rational, analytical) processes, while a longer time is associated with the activation of Type 2 processes and the assessment of the long-term perspective.